1998
DOI: 10.1128/iai.66.1.43-51.1998
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flagella in Pathogenesis ofPseudomonas aeruginosaPulmonary Infection

Abstract: Pseudomonas aeruginosa strains are opportunistic pathogens associated with infections in immunocompromised hosts and patients with cystic fibrosis. Like many other mucosal pathogens,P. aeruginosa cells express flagella which provide motility and chemotaxis toward preferred substrates but also provide a ligand for clearance by phagocytic cells. We tested the role of flagella in the initial stages of respiratory tract infection by comparing the virulence of fliC mutants in a neonatal mouse model of pneumonia. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(167 citation statements)
references
References 32 publications
3
163
0
1
Order By: Relevance
“…This suggested Caco-2 cells as a suitable in vitro model for studying flagellin signalling. Using that model, flagellin signalling was shown to be mediated strictly through TLR5, and not an alternate receptor such as the ganglioside asialoGM1, which had been reported by others to function as a alternative receptor for bacterial flagellin on airway epithelial cell lines (DiMango et al, 1995;Feldman et al, 1998;Adamo et al, 2003;Ogushi et al, 2004;West et al, 2005). Studies in this model further showed that EHEC flagellin was both necessary and sufficient for upregulating CXCL8 in the context of EHEC infection.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This suggested Caco-2 cells as a suitable in vitro model for studying flagellin signalling. Using that model, flagellin signalling was shown to be mediated strictly through TLR5, and not an alternate receptor such as the ganglioside asialoGM1, which had been reported by others to function as a alternative receptor for bacterial flagellin on airway epithelial cell lines (DiMango et al, 1995;Feldman et al, 1998;Adamo et al, 2003;Ogushi et al, 2004;West et al, 2005). Studies in this model further showed that EHEC flagellin was both necessary and sufficient for upregulating CXCL8 in the context of EHEC infection.…”
Section: Discussionmentioning
confidence: 57%
“…Flagellin from Pseudomonas aeruginosa was reported to activate NF-κB production in airway epithelial cells by signalling through either TLR5 or the ganglioside asialoGM1 (DiMango et al, 1995;Feldman et al, 1998;Adamo et al, 2003), raising the possibility that flagellin induction of the NF-κB target gene CXCL8 in colon cancer cell lines might take place through an alternative receptor. However, this was not the case.…”
Section: Epithelial Cell Encounter With Ehec Flagellin At the Apical mentioning
confidence: 99%
“…We propose that TLR5 is unlikely to be the initial receptor for flagella as the flagellin domain that binds TLR5 forms part of the core of the flagellar filament (Eaves-Pyles et al, 2001;Smith et al, 2003), and thus is not exposed in the native structure and TLR5 is usually located on the basolateral surface of enterocytes (Gewirtz et al, 2001). Other epithelial receptors or coreceptors for flagella have been proposed, including TLR2 (Adamo et al, 2004), gangliosides (Feldman et al, 1998;McNamara et al, 2001;Ogushi et al, 2004) and mucin (Lillehoj et al, 2002). Recently it has been shown that H7 flagella bind mucus potentially via Muc2 (Erdem et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these Ca 2+ responses involve binding of flagellin to TLR(toll-like receptor)-5, a receptor belonging to the TLR family of pattern-recognition molecules crucial for innate immunity (Fearon and Locksley, 1996;Zhang and Ghosh, 2001), and that was described to act as receptor for bacterial flagellin (Takeda et Akira, 2001), is unclear. In the case of P. aeruginosa, the flagellin was also shown to bind to asialoGM1 (ASGM1), a glycolipid receptor (Feldman et al, 1998;Mc-Namara et al, 2001;Fig. 2).…”
Section: Ca 2+ -Dependent Activation Of Nf-jb By Bacterial Pathogensmentioning
confidence: 99%